Survival outcomes after neoadjuvant letrozole and palbociclib versus third generation chemotherapy for patients with high-risk oestrogen receptor-positive HER2-negative breast cancer. (May 2022) - Delaloge, Suzette; Dureau, Sylvain; D'Hondt, Véronique; Desmoulins, Isabelle; Heudel, Pierre-Etienne; Duhoux, Francois P.; Levy, Christelle; Lerebours, Florence; Mouret-Reynier, Marie A.; Dalenc, Florence; Frenel, Jean-Sébastien; Jouannaud, Christelle; et al.
Abstract: Background: Besides their development as additional adjuvant treatments, CDK4/6 inhibitors combined with endocrine therapy could represent less toxic alternatives to chemotherapy in postmenopausal women with high-risk oestrogen receptor-positive, HER2-negative breast cancer currently a candidate for chemotherapy. The multicentre, international, randomised phase 2 NEOPAL trial showed that the letrozole-palbociclib combination led to clinical and pathological responses equivalent to sequential anthracycline-taxanes chemotherapy. Secondary objectives included survival outcomes. Methods: Secondary end-points of NEOPAL included progression-free survival (PFS) and invasive-disease free survival (iDFS) in the intent-to-treat population. Exploratory end-points were overall survival (OS) and breast cancer specific survival (BCSS) in the intent-to-treat population, as well as iDFS, OS and BCSS according to the administration of chemotherapy. Results: Hundred and six patients were randomised. Pathological complete response rates were 3.8% and 5.9%. Twenty-three of the 53 patients in the letrozole-palbociclib arm received postoperative adjuvant chemotherapy. At a median follow-up of 40.4 months [0–56.6], 11 progressions have been observed, of which three were in the letrozole-palbociclib and 8 in the control arm. PFS (HR = 1.01; [95%CI 0.36–2.90], p = 0.98) and iDFS (HR = 0.83; [95%CI 0.31–2.23], p = 0.71) did not differ between both arms. The 40 months PFS rate was 86.7% [95%CI 78.0–96.4] and 89.9% [95%CI 81.8–98.7] in letrozole-palbociclib and control arms, respectively. Outcomes of patients who did not receive chemotherapy were not statistically different from those who received it. Conclusions: NEOPAL suggests that a neoadjuvant letrozole-palbociclib strategy may allow sparing chemotherapy in some patients with luminal breast cancer while allowing good long-term outcomes. Larger confirmatory studies are needed. Graphical abstract: Image 1 Highlights: First CDK4/6 neoadjuvant randomised trial to report survival outcomes. NEOPAL trial compared neoadjuvant Letrozole Palbociclib versus chemotherapy. Pathological complete response rates were identically low (3.8% and 5.9%, respectively). Progression-free survival (HR = 1.01; [95%CI 0.36–2.90], p = 0.98) did not differ between both arms. Invasive disease-free survival (HR = 0.83; [95%CI 0.31–2.23], p = 0.71) did not differ between both arms.